Developing Picture Story Books to Increase Reading Interest in Fourth Grade Students - Nurhidayati, Titin; Satinem, Yohana; Lontoh, Willy (Global Education Journal, 2025)
Learning is an interaction between educators and students in carrying out the learning process. This study aims to develop a picture story book as a learning medium to increase the reading interest of fourth grade students of SD Negeri 74 Lubukinggau that is valid, practical and effective. This study uses the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation) with data collection techniques through questionnaires, tests and documentation. The trial subjects consisted of 21 students and class teachers. The results of the development and research show that: 1) The resulting picture story book can be declared valid for use in increasing students' reading interest with a language validation score of 0.90 (high category), media validation of 0.85 (high category), and material validation of 0.95 (high category). 2) the level of practicality of the media, both from teacher and student assessments, meets the criteria of "very practical" with an average score of 90.95%. In detail, the results of the teacher's practicality trial reached 96% (very practical), the small group trial 88% (very practical), and the field test trial 88.48% (very practical). 3) The level of media effectiveness based on student assessments showed an N-Gain of 0.71 (high category). Thus, the resulting picture storybook is suitable for use as a learning medium to increase students' interest in reading.